Tubularized incised plate urethroplasty with or without stent in Hypospadias repair: a systematic review and meta-analysis - Seyed Abdollah Mousavi; Mohsen Aarabi (Mazandaran University of Medical Sciences, 2014)
Numerous methods for repair of hypospadias have been introduced. The technique of Tubularized Incised Plate urethroplasty has gained widespread acceptance. In the classical method of Tubularized Incised Plate urethroplasty, to divert urine flow and preventing urethral stenosis, a stent was used, but its necessity is questionable for some surgeons. In this paper we systematically compared the results of operations in different studies. Searching the databases such as PubMed, SCOPUS, and Google Scholar was done and articles found from January 1994 to September 2013 were included. Then articles about the impact of use or non-use of urinary catheters on surgical outcomes were analyzed. By reviewing 168 studies related to repair of hypospadias with TIP, we selected 11 studies that met our inclusion criteria which did not use a stent. A total of 708 children had urethroplasty using the TIP method without stent. The overall complication rate such as meatal stenosis and fistula compared with stents was not significant. It could tell us that at least in some cases especially in distal types, use of stent can be avoided, because its least benefit would be reduction of bladder spasm and urinary tract infections.